DEPELOVMENT OF A COMPANION ANDRAGOGICAL COMPETENCY ASSESSMENT INSTRUMENT - Daddy Darmawan; Adi Irvansyah; Rahmat Syah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This study aims to develop an andragogical competency assessment instrument. The research method used is a development method that produces a product in the form of a companion andragogical competency assessment instrument. The development of the instrument through some stages, namely the first phase of the instruments,the second phase of judgment instrument by experts, the third phase testing instruments and the fourth analysis item. A sample of respondents taken by using purposive sampling as many as 200 assisted residents in DKI Jakarta. Data Analysis research using the descriptive confirmatory statistical descriptive analysis of factors to find the validity and the formation of factor characteristics and reliability is determined by Alpha Cronbach more than 0,70. The assessment instrument has been declared valid and reliable. The first stage of this development is to compile an instrument based on theoretical studies and obtain 5 dimensions of standard andragogical competence on the principles and 5 dimensions of the mentoring process. The second stage was carried out by the expert justment of the instrument by providing an assessment and revising the grid and instrument items. The content validity was tested by experts and a good aiken statistical index. The third stage is testing in the field and the fourth stage is conducting factor analysis with the results of the value of the construct validity carried out by exploratory and confirmatory factor analysis where the Confirmatory Factor Analysis test results show 34 valid and reliable items.